Analysis of Renewable Energy Potential for Sustainable Tourism Development in Cipanas Galunggung Geothermal Area, Tasikmalaya Regency, Indonesia - Faridah, Linda; Risnandar, Muhammad Aris; Nurdiansyah, Rian (Universitas Muhammadiyah Jakarta, 2024)
This research analyzes the potential of renewable energy, particularly geothermal energy, for sustainable tourism development in the Cipanas Galunggung area, Tasikmalaya Regency, Indonesia. The study employs a qualitative approach with secondary data analysis and literature review. Results indicate that the Cipanas Galunggung geothermal area possesses significant potential for renewable energy development to support sustainable tourism. The existing 30 MW geothermal power plant serves as a foundation for further development. Integration of renewable energy in tourism development can enhance energy security, reduce environmental impact, and create new attractions. However, challenges remain in terms of investment, infrastructure, and policy coordination. This study recommends a collaborative approach involving government, private sector, and local communities to optimize the utilization of renewable energy for sustainable tourism growth in the region. The research provides empirical evidence that geothermal energy development in the Cipanas Galunggung area can be a sustainable solution to meet energy needs while enhancing tourist attractions. However, further studies are needed on the social and cultural impacts of geothermal energy development on local communities. Additionally, it is important to involve the community in planning and managing geothermal energy projects to ensure equitable distribution of benefits